2024
DOI: 10.1109/jsen.2024.3394651
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensing System Based on an All-Fiber Photothermal Microcell

Matej Njegovec,
Jure Javornik,
Simon Pevec
et al.

Abstract: This paper presents an all-fiber, miniature Fabry-Perot gas sensor based on photothermal absorption spectroscopy with a custommade and cost-efficient interrogation system. The sensing gas microcell has a diameter of 125 μm, a length of 1 mm, and allows for free gas exchange within the optical resonator through micromachined slits. High light intensity and confinement is ensured by delivering the excitation light directly into the gas microcell through a lead-in singlemode fiber. This enhances the photothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…Recently, Krzempek et al have used miniaturized fibre-based Fabry Perot cavity sensors to retrieve the PTS signal in a proof-of-concept measurement of methane [ 12 ]. Similarly, Njegovec et al have demonstrated an all-fibre PTS gas sensor, comprising a probe fibre, a slotted capillary and an excitation fibre [ 13 ], and Yao et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Krzempek et al have used miniaturized fibre-based Fabry Perot cavity sensors to retrieve the PTS signal in a proof-of-concept measurement of methane [ 12 ]. Similarly, Njegovec et al have demonstrated an all-fibre PTS gas sensor, comprising a probe fibre, a slotted capillary and an excitation fibre [ 13 ], and Yao et. al.…”
Section: Introductionmentioning
confidence: 99%